Capital social e sintomas depressivos em idosos do sul do Brasil - Quatrin, Louise Bertoldo (Universidade do Vale do Rio dos Sinos, 2012)
Recent studies have suggested that participation in groups, solidarity and willingness to intervene for common good may have a positive effect on mental health of individuals and groups. This dissertation presents the results of piece of research conducted with elderly in in a small town in the South of Brazil. The aim was to investigate the association between depressive symptoms and social capital. It is a cross-sectional population-based study with 1.007 elderly people. Structured interviews were conducted at the household of the elders, people aged 60 or more years. Depressive symptoms were assessed by geriatric depression scale using the cuttoff of 11 points or higher. Social capital was measured by the collective efficacy scale and by a single item about participation in groups. Data analysis used Poisson Regression Method to obtain crude and adjusted prevalence ratios (PR). The sample consisted mostly of elder women (63%), caucasian (96%) and married (64%). Average income, age and years of schooling were 73 years old (DP=4), BR$ 1,836 (DP= 2,170) and 5 years (DP=4) respectively. After controlling of demographic, socioeconomic, behavioural and health related variables, participants who reported low collective efficacy in their place of residence had a prevalence of depressive symptoms twice as big than those reporting high efficacy (RP=1.40; IC95% 1.03 – 1.91; p<0.001). Similarly, elders who didn't participate on any group reported outcome prevalence about 64% higher than the ones who participated on one or more groups (RP=1.64; IC95% 1.27 – 2.12; p<0.001). The association reported here suggests that the creation and participation in networks and groups may be an important strategy to promote the mental health of elderly people.
The potential influence of social capital in the presence of depressive symptoms in the elderly in Southern Brazil
Keywords: Envelhecimento; Depressão; Participação comunitária; Participação social; Aging; Depression; Social medicine; Social participation; ACCNPQ::Ciências da Saúde::Saúde Coletiva